TANTANGAN TUGAS WAKIL KEPALA DAERAH SUATU TINJAUAN YURIDIS MENURUT UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - ibrahim (Madani Legal Review, 2020)
The position of Deputy Regional Head is regulated in Law No. 23 of 2014,. However, this Law does not explicitly regulate the duties of Deputy Regional Heads because almost all of their duties are attached to the duties of regional heads by using the term "assisting" regional heads. The problem is in the practice of governance in several regions, the regional head was impressed in fact, they tend to be reluctant to be assisted by their representatives. The data analysis method used in this study is descriptive qualitative. The method of study uses the method of literature study with a descriptive approach. The term used in Article 66 of Law no. 23 of 2014 concerning Regional Government, is the word "help", so this word has the potential to be twisted for subjective interests that are short-term in nature. Especially in the implementation of local government pragmatic interests can not be avoided so that it can cause tug of interest so that in the administration of government does not run effectively. It is expected that the presence of provisions governing the task of the deputy regional head will be an instrument of problem solving, in terms of overcoming the severity of the task tasks of the regional head in the administration of regional government.